A Study on Push-Pull Analysis Associated with Awkward Posture among Workers in Aerospace Industry - Norhidayah, Hashim; Kamat, Seri Rahayu; Isa, Halim; Mohd Shahrizan, Othman (Sun Publications, 2014)
In aerospace industries, many working tasks required their workers to perform works in push-pull activity. It is associated with an awkward posture. The awkward posture is a practical working posture when joints are not in neutral position. Furthermore, the workers need to push or pull the mould in a long distance into a workplace. If the workers perform the activity continuously throughout the working hours, they may be experienced back pain problem. The objective of this study is to measure the maximum acceptable initial force and sustained force for push-pull activity while workers perform their tasks. Besides that, this study also wants to identify which activity can endure longer between push or pull activity. Moreover, this study measures the comfort level of working posture. The acceptable initial force and sustained force were measured using Push-Pull Analysis, expressed in Newton, N. The comfort level is measured using Rapid Upper Limb Assessment (RULA) Analysis, expressed in scoring level. Both of these assessments are analysis tools Computer-Aided Three-Dimensional Interactive Application (CATIA) software. Six production workers from manufacturing department were participated as subjects. The results show the maximum acceptable initial force for push task is 433.942N and pull task is 396.691N. While, the sustained force for push task is 333.465N and pull task is 318.317N. Referring to the results, pushing activity can endure longer than pulling activity while workers perform their tasks. While the comfort level for this working posture is seven. Based on this study, the authors concluded that push-pull activity can lead to the back pain problem for workers in aerospace industry. It’s was influenced by the work activity, work load, work duration of awkward posture and distance between workplace.